Student communication and study habits of first-year university students in the digital era | Communication étudiante et habitudes d'étude des étudiants universitaires de première année à l'époque numérique - Eliana Esther Gallardo-Echenique; Mark Bullen; Luis Marqués-Molías (The Canadian Network for Innovation in Education (CNIE), 2016)
This paper reports on research into how first-university students communicate with peers and professors and their general study habits and to examine the possible relationship between students' use of digital technologies. The research is positioned in the interpretive paradigm. We conclude that most students feel comfortable with digital technologies and they see Facebook/MySpace as more about connecting and interacting with friends than for academic communication. Results show that students prefer face-to-face communication for both academic/school and social communication. Regarding study habits, students prefer to learn by themselves, work independently and to study at home. Cet article présente la recherche sur les habitudes d'étude des étudiants universitaires, leur usage des technologies numériques et leur façon de communiquer entre eux et avec leurs professeurs. Nous concluons que la plupart des étudiants se sentent à l'aise avec les technologies numériques et qu'ils utilisent les médias sociaux pour leurs liens et interactions avec leurs amis plutôt que pour la communication scolaire. Les étudiants préfèrent les communications en personne en ce qui a trait aux communications scolaires et sociales et préfèrent apprendre par eux-mêmes, travailler de manière autonome et étudier à la maison.